Reliability Assessment of an Improved Single‐Input Switched‐Capacitor Boost 7/9‐Level Inverter Suitable for Renewable Energies - Armin Ghelichi; Kazem Varesi; Milad Khoubrooy Eslamloo (Engineering Reports)
ABSTRACT This paper proposes an improved single‐source switched‐capacitor inverter that can operate either as 7 or 9‐level inverter based on its capacitors' charging scenario. The proposed inverter utilizes single DC supply, two capacitors, ten switches (all unidirectional) and a single diode to provide a triple/quadruple boosting factor in its seven/nine‐level operation mode. In 7‐level (7 L) operation mode, both the capacitors are charged to identical voltage value (equal to the source voltage), but in 9‐level (9 L) mode, the capacitors are charged to different voltages. Any load type with variety of power factors can be supplied by the proposed inverter. The capacitors' impulsive charging current issue has been solved by employing compact (small‐inductor based) and low‐cost soft‐charging L‐D cells. The reliability assessments have also been performed on the proposed 7/9‐level inverter. The superiority of the proposed inverter over its similar counterparts have been verified by comprehensive comparative analysis. The experimental outcomes have also been provided to make sure of correct performance of proposed inverter.